Time-Irreversibility and Existence and Uniqueness of Solutions of Problems in Linear Viscoelasticity - Matarazzo, G. (Український математичний журнал, 2000)
We study a problem of linear viscoelasticity for the case where the relation between the Cauchy stress and strain tensors is described by a linear integral relation. Theorems on the existence and uniqueness of a solution of the problem are proved. Вивчається задача теорії пружності для випадку, коли зв'язок між тензорами напруги та деформації Коші описується за допомогою лінійного інтегрального співвідношення. Доведено теореми про існування та єдиність розв'язку відповідних задач.